PENGARUH PENERAPAN MODEL PEMBELAJARAN VARIATION STIMULUS TERHADAP PRESTASI BELAJAR PRODUKTIF AKUNTASI SMK MUHAMMADDIYAH 2 BANDAR LAMPUNG - Zainal, Vetri Yanti (Lentera: Jurnal Ilmiah Kependidikan, 2015)
Accounting productive subjects should be given to all the students of SMK to equip with the ability to think logically, creative, intelligent, careful, critical, innovative, systematic and ability to cooperate. The fact class materials have been delivered to students are not fully understood by the students, because the students kejenuhnan level higher than the interest in studying accounting.The purpose of this study was to determine the extent of the influence of variation stimulus to productive accounting student learning achievement and determine differences in accounting productive learning achievement among students who use the stimulus variation learning model that does not use a learning model variation stimulus.Based on the hypothesis testing that has been done using the formula ttes and consulted on ttab with 5% significance level indicates that thit> ttab this means that there is the influence of variation stimulus application of learning models to the learning achievement of students earning accounting. From testing the equality of two average can result in thit <tdaf the real level of 0.05. This shows that the test results is quite significant and can receive provisional estimates the authors propose using stimulus variation application of learning models will be a positive influence in improving the learning outcomes of economic accounting.